2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5461919
|View full text |Cite
|
Sign up to set email alerts
|

MeasuRouting: A Framework for Routing Assisted Traffic Monitoring

Abstract: Monitoring transit traffic at one or more points in a network is of interest to network operators for reasons of traffic accounting, debugging or troubleshooting, forensics, and traffic engineering. Previous research in the area has focused on deriving a placement of monitors across the network towards the end of maximizing the monitoring utility of the network operator for a given traffic routing. However, both traffic characteristics and measurement objectives can dynamically change over time, rendering a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In each set of topology, we first calculate multiple paths for every OD (origin-destination) pair nodes to simulate the (ECMP)-like algorithm in practical scenarios, and run DisMR on those multiple paths. Our simulations have three goals: (1) determine good parameters for the algorithm to quickly reach equilibrium state without significant oscillations; (2) show that the measurement gain of the network at equilibrium state is close to the offline maximum achievable gain calculated by static centralized MeasuRouting; (3) show that it indeed improves measurement gain in dynamic traffic scenario compared to static centralized MeasuRouting.…”
Section: Performance Evaluationmentioning
confidence: 81%
See 2 more Smart Citations
“…In each set of topology, we first calculate multiple paths for every OD (origin-destination) pair nodes to simulate the (ECMP)-like algorithm in practical scenarios, and run DisMR on those multiple paths. Our simulations have three goals: (1) determine good parameters for the algorithm to quickly reach equilibrium state without significant oscillations; (2) show that the measurement gain of the network at equilibrium state is close to the offline maximum achievable gain calculated by static centralized MeasuRouting; (3) show that it indeed improves measurement gain in dynamic traffic scenario compared to static centralized MeasuRouting.…”
Section: Performance Evaluationmentioning
confidence: 81%
“…In contrast to MeasuRouting [2],we assume independent uniform sampling across all participated routers, where each router independently selects a packet with a sampling probability (typically between 0.001 and 0.01) and aggregates the selected packets into flow records (e.g., via Netflow [1]). Let S a be the given fixed sampling rate at every arc a ∈ A where A stands for the set of all arcs in the network.…”
Section: Adaptive Traffic Measurement Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekar et al suggested approaches for NIDS or NIPS deployment [30] through selectively monitoring packets at different nodes and load balancing [12] through traffic replication and aggregation. Raza et al introduced an approach to route packets to network monitoring points [29]. Even though our work is similar in that our work finds new routing paths for security devices, our work provides in-depth analysis of routing algorithms, and provides more diverse routing and response strategies considering security devices.…”
Section: Related Workmentioning
confidence: 93%
“…Software-defined networking (SDN) adopts the concept of programmable networks by using a logically centralised management, which represents a simplified solution for complex tasks such as traffic engineering [1], network optimisation [2] and orchestration [3]. Furthermore, dealing with modern network applications requires more scalable architecture which should be able to provide reliable and sufficient services based on a specific traffic type [4].…”
Section: Introductionmentioning
confidence: 99%